Rejection of lie as a condition of pedagogical dialogue - Seweryn Łukasz Leszczyński (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introduction: Lying is a constant threat to every educational relationship, the essence of which is the pedagogical dialogue. Without rejecting the lie, one cannot speak of a true student-teacher relationship. The aim of the research: The article aims to defend the thesis about the necessity to reject lies in the pedagogical dialogue. The aim is also to introduce the notions of the human person, pedagogical dialogue and lies as understood by Wojciech Chudy, the creator of ethical and Christian personalism. State of knowledge: The topics of pedagogical dialogue were undertaken among others by Jerzy Zieliński, Edward Torończak, Jarosław Gara, Andrzej Bronk, Marian Śnieżyński, Janusz Tarnowski, Anna Szudra-Barszcz, Wojciech Chudy. Wojciech Chudy developed a comprehensive view of the philosophy of lies. The creator of the concept of the human person in the ethical-Christian personalism analyzed here is Wojciech Chudy. Summary: The condition for the existence and conduct of any pedagogical dialogue is the rejection of lies. Even the slightest attempt to lie can lead to a tendency to distance ourselves from the truth of the interpersonal and educational relationship. The condition for conducting a pedagogical dialogue is the affirmation of the truth.